Ceramics in Picasso’s Work as a Whole. - Haro-González, Salvador (Yoku Moku Museum, 2024)
Los trabajos de Picasso en cerámica no constituyen un pasatiempo pasajero ni un intermedio lúdico en su obra, sino que forman parte del conjunto indisoluble que constituye la obra toda del artista malagueño. en este ensayo se abordan diferentes cuestiones que pretenden demostrar esta hipótesis, conectando las cerámicas de Picasso con otras obras en distintas disciplinas, con las que están en relación directa a veces a nivel formal, otras técnico, temático o conceptual.
ピカソ作品の総体に占めるセラミック
Ensayo publicado en inglés y japonés. Texto encargado por el Yoku Moku Museum para el catálogo de la exposición Picasso ceramics: art of mitate
El museo autoriza que se suba al repositorio. Copio correo recibido el 5 de enero a tal efecto: Dear Salvador, Thank you very much for your message, and please excuse the delay in my reply. I am glad to tell you that we have received full approval from our Director, Ms Yoko Fujinawa, regarding the reposting of your catalogue text on the university repository. We are more than happy for it to be shared again, and it is in fact a very welcome development for us as well. Yoko asked me to convey her warm thanks to you. While the past months have naturally been a difficult time for her, she is now gradually finding her way forward and looking ahead. I very much hope, as she does, that we may continue to enjoy the same friendship and mutual trust in the years to come. I will send you the PDF shortly, and at the same time I will be happy to share some information about our next exhibition, as you kindly asked. Could I kindly ask you to allow me about half a day to prepare and forward everything to you? With my warmest thanks once again, and all best wishes, TOMIYASU Reiko r.tomiyasu@yokumokumuseum.com Chief Curator YOKU MOKU MUSEUM 6-15-1 Minami-Aoyama, Minato-ku, Tokyo, Japan Tel: +81 (0)3 3486 8000 https://yokumokumuseum.com
Keywords: Picasso, Pablo - Crítica e interpretación; Picasso; Cerámica; Obra como conjunto